al-'Allamah al-Shaykh Ibn Abi Nabhan al-Kharusi : hayatuhu wa-atharuh - al-Kharusi, Khalid ibn'Abd Allah ibn Sayf (Masqat : Dhakirat'Uman, 2017)
Ibadites; Africa, North; biography.
Includes bibliographical references (unnumbered pages 73-page 75) and indexes.
Keywords: Ibn Khamis, Ja'id.; Kharijites -- Oman -- Biography; Ibadites -- Oman -- Biography